2020
DOI: 10.1038/s41598-020-79399-4
|View full text |Cite
|
Sign up to set email alerts
|

Deposited ultra-thin titanium nitride nanorod array as a plasmonic near-perfect light absorber

Abstract: The transmittance, reflectance, and extinctance that correspond to the localized plasmonic resonance within TiN nanorods were investigated. The obliquely deposited TiN nanorod array shows polarization-independent admittance matching to air. Unlike noble metal nanorods, the near-field localized longitudinal and transverse plasmonic resonance of TiN nanorod arrays present polarization-dependent light extinction in the far field. The longitudinal plasmonic mode presents stronger extinction than transverse plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, some refractory metallic materials become excellent candidates, such as titanium. It has been reported that an average absorption of more than 95% in the wavelength range of 400 nm-900 nm was achieved by using titanium [17][18][19]. As a refractory material, the melting point of metal titanium is as high as 1668 • C. Because of its excellent optical loss characteristics, titanium shows a higher light absorption efficiency in a fairly broad wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some refractory metallic materials become excellent candidates, such as titanium. It has been reported that an average absorption of more than 95% in the wavelength range of 400 nm-900 nm was achieved by using titanium [17][18][19]. As a refractory material, the melting point of metal titanium is as high as 1668 • C. Because of its excellent optical loss characteristics, titanium shows a higher light absorption efficiency in a fairly broad wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…Due to plasmonic effects, TiN nano-square rings [12] are regularly distributed on SiO 2 films that are coated on silicon to provide high absorptance for visible wavelengths. Like TiN nanosquare ring arrays, glancing-angle deposited TiN nanorod arrays also exhibit broadband and wide-angle admittance matching [13].…”
Section: Introductionmentioning
confidence: 99%